Pelayanan Kesehatan Komprehensif Pascabencana di Koto Alam, Palembayan, Kabupaten Agam - Wendy Armi; Fuccy Utamy Syafitri (Departemen Budidaya Tanaman Perkebunan, Fakultas Pertanian, Universitas Andalas, 2026)
Hydrometeorology disasters significantly disrupt access to essential health services, particularly for vulnerable groups such as children, women of reproductive age, older adults, and patients with chronic diseases. In late November 2025, flash floods and landslides (galodo) struck 16 sub-districts in Agam Regency, West Sumatra, killing more than 180 people in Kecamatan Palembayan alone and displacing thousands of residents. Universitas Andalas (UNAND), through its Faculty of Medicine, responded by deploying specialist medical teams as part of a structured disaster response program coordinated by the Institute for Research and Community Service (LPPM UNAND). This community service report describes the activities of one such team operating on 20 December 2025 at two service points in Koto Alam, Palembayan: Posko Nagari Koto Alam (SD 35 Gumarang) and Rumah Singgah 01. Services included patient registration, anamnesis, physical examination, clinical diagnosis, medication dispensing, individual health education, and referral recommendation. A total of 87 patients were served, with women comprising a larger proportion and ages ranging from 2 to 88 years. Service needs included general complaints, respiratory problems, chronic disease management (hypertension, asthma), gynaecological complaints, nutritional support for children, and ophthalmological issues. Medications were prepared across four clinical domains: paediatrics, obstetrics and gynaecology, internal medicine, and ophthalmology. This report also analyses challenges commonly encountered in post-disaster health management, including logistics gaps, disrupted care continuity, inadequate data recording, insufficient vulnerable-group services, and coordination difficulties, as well as evidence-based solutions from disaster health literature. Post-disaster community health services at field posts and transit shelters play a vital role in maintaining care continuity; however, strengthening logistics, referral pathways, recording systems, and interagency coordination remains essential.